The diversity of aquatic insects in the Tsitsikamma region, with implications for aquatic ecosystem conservation - Bellingan, Terence Andrew (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2011)
As a result of research carried out within the last decade to assess the diversity of macroinvertebrates of the Salt River in the Western Cape Province, South Africa, surveys of macroinvertebrates of 20 sites on 11 selected rivers from the same mountain range source were undertaken. This was done to make a preliminary assessment of the conservation status of the rivers of this region. Aquatic insects from the orders Ephemeroptera, Odonata, Plecoptera, Megaloptera, Trichoptera and the dipteran family Simuliidae were collected using techniques to maximize the number of taxa found. The insects collected were identified to species level where possible. Water physicochemical parameters were recorded at all sites for each sampling trip to characterize these rivers and to establish a set of baseline data for future comparisons. These parameters included measurements made on site and analysis of the concentrations of all the major ions in water samples in the laboratory. Multivariate analyses including Principle Components Analysis and Canonical Correspondence Analysis were used to reveal patterns within the water physicochemistry and species distributional data. Results include the identification of 123 species from 70 genera and 30 families. A total of 31 species were found to be undescribed, of which 17 were not previously collected and are thus completely new to science. In addition, four of these species could not be placed into any known genus. The analysis of water physicochemistry showed a clear distinction between rivers of Table Mountain sandstone and Bokkeveld shale origin. Downstream effects of anthropogenic influences were discernable too. Distinct macroinvertebrate assemblages were found based upon stream order and water chemistry composition. pH proved to be the most important driver of invertebrate assemblage composition. The high levels of endemism of the macroinvertebrates found within the upper reaches of these rivers and their degree of ecological specialization make these systems a priority for the conservation of aquatic biodiversity on a national and global scale.
Keywords: Aquatic insects -- South Africa -- Tsitsikamma; Aquatic insects -- Classification -- South Africa -- Tsitsikamma; Aquatic ecology -- South Africa -- Tsitsikamma; Ecosystem management -- South Africa -- Tsitsikamma; Stream conservation -- South Africa -- Tsitsikamma